Prevalence of the depression among heart failure patients in Ethiopia, 2024: A systematic review and meta-analysis - Birhaneslasie Gebeyehu Yazew; Workineh Tamir Shitu; Mohammed Hassen Salih; Zewdu Bishaw Aynalem; Haile Workye Agazhu; Daniel Adane Endalew (PLoS ONE, 2025)
Background Heart failure (HF) is a major clinical condition contributing to high morbidity, mortality, and healthcare burden. Depression is increasingly recognized as a nontraditional risk factor for HF. However, data on its prevalence among HF patients in Ethiopia remain limited. This study aimed to estimate the pooled prevalence of depression in Ethiopian HF patients. Methods The study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, using data abstraction from various electronic sources (PubMed, Web of Science, Google Scholar, Scopus, Science direct, African journal, and online University repositories studies). Studies reporting the prevalence of depression among heart failure patients found until 28th November, 2024 were included. Analysis was conducted using STATA version 17 software, with assessment of heterogeneity and publication bias. A random-effects meta-analysis model was used to estimate the pooled prevalence of depression. Results This study revealing a pooled prevalence of depression among Heart failure patients in Ethiopia is 43.93%. Subgroup analyses based on region, type of institution, and sampling method showed different prevalence rates: the Southern Nations, Nationalities, and Peoples’ Region had the highest rate at 60.13%, while Addis Ababa had the lowest at 35.18%. In terms of study institution types, teaching hospitals reported the highest prevalence at 46.81%, whereas referral hospitals showed the lowest rate at 31.05%. When considering sampling techniques, consecutive sampling yielded the highest prevalence at 55.09%, compared to just 15.40% for systematic random sampling. The analysis indicated a publication bias (p = 0.003), which warranted the use of trim and fill methods. Conclusion and recommendations The rate of depression among heart failure patients in Ethiopia is notably high, highlighting the necessity for targeted interventions from the Ministry of Health to tackle this concern. It is essential to create multi-sectorial strategies that offer context-specific solutions, such as rehabilitation programs, to help reduce depression in heart failure patients. The review protocol was registered in PROSPERO ID: CRD42023405077.